Can debt overhang help explain the declining growth rate of investment in China?. Issue 2 (19th January 2020) - Liu, Lili; Cebula, Richard J.; Foley, Maggie; Peng, Fangping
ABSTRACT: In this study, we investigate whether debt overhang may contribute to explaining the declining growth rate of investment in China. By using firm-level data, we find a nonlinear firm debt–investment relationship and derive thresholds beyond which debt has a negative and significant impact on investment, which supports the theory of debt overhang.